Movement and personality development - Aida M. Aylamazyan (Национальный психологический журнал, 2017)
The paper discusses the role of the movement in the process of shaping the personality, its importance as a mechanism for personality development is considered. The issue of the movement has always occupied a central place in Russian psychology. However, subsequently the movement began to be considered primarily as an executive action in human life. The role of movement in personality development can vary depending on the level it occupies in the hierarchical structure of activity, and also on the type of movement, its character, and the way it is constructed. Under certain conditions, the movement can express the attitude of the subject to the surrounding world and people. Many foreign and Russian psychologists point to a special place of the postural tonic component of the motor movement, the posture in personal regulation. The posture reflects his/her personal attitudes, the system of relationships, and, above all, the emotional attitude or emotional assessment of the current situation, the interest in the actions performed. Mastering the tonic level of motor management is based on the emotional regulation, so the ability to regulate one’s own pose is an important stage in the personality development. Posture tonic regulation of motor movements in humans reveals a qualitatively different character than in animals, this being due to the person’s facing the task of mastering his’her posture, arbitrary retention of the body in one or another position. Maintaining a vertical posture requires constant activity at an arbitrary and involuntary level of mental regulation. Mastering the posture of an unstable equilibrium presupposes the emergence of the «I» and is the last stage of the development. The way a person solves the motor task of maintaining the vertical position of the body reflects his/her specific personal strategy or attitude.